BUNGA DAN BUAH GUGUR PADA TANAMAN MANGGIS (GARCINA MANGOSTANA L.) ASAL BIJI DAN SAMBUNGAN - RAI, I NYOMAN (AGRITROP; Vol. 26, No. 2 Juni 2007, 2012)
Grafted mangosteen tree have a shorter juvenile period than that of the seedling trees because it starts to flower earlier. However, productivity of the grafted trees is low because number of flowers and fruits drop is high. The research was conducted to study the difference of flowers and fruit drop between seedling and grafted trees related to N, P, and K plant nutrition levels and position of growing flower and fruit. The result showed that percentage of flowers and fruits drop of grafted mangosteen (14,65% and 85,38%) were higher than those of seedling plants (6,93% and 16,58%). Yield of grafted tree (2,17 kg/plant) was significanly lower than that of seedling (7,07 kg/plant) exhibited by low number of harvesting fruit. N, P, and K nutrition leaf levels had no effect on flower and fruit number drop, not only on grafted trees, but also on seedling trees. Flowers and fruits which grow at the basal of tree and/or branch drop were hihger than those of midle and upper part of trees and branchs.
Keywords: mangosteen, seedling, grafted tree, flower drop, fruit drop